Bilateral thalamic anaplastic glioma: Case report - (:unkn) unknown (My University, 2008)
The authors report on a patient with bilateral thalamic anaplastic glioma diagnosed via stereotactic brain biopsy. A 54-year-old man presented with headache and gradually increasing personality changes. Computed tomography and Magnetic Resonance (MR) of the brain demonstrated bilateral thalamic lesions. MR Spectroscopy of the thalamic lesions showed an increased Choline and creatinin peak and a glial tumor was diagnosed radiologically. A stereotactic brain biopsy was performed. Pathological examination revealed anaplastic astrosytoma grade III (World Health Organisation Classification 1993). The patient was referred to radiation therapy. Gliomas of the thalamus are rare and Bilateral Thalamic Anaplastic Gliomas are less defined. Surgical treatment is limited since eloquency of the region and stereotactic biopsy is necessary. The choice of treatment is radiotherapy.
Keywords: Bilateral involvement; Glioma; Thalamus